ANALISIS KELAYAKAN FINANSIAL USAHA FRANCHISE O’CHICKEN DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - sti Kurniawati E; Yusmini Yusmini; Susy Edwina (Fakultas Pertanian, Universitas Riau, 2018)
This study aimed to analyze the financial feasibility in terms of Net Present Value (NPV),Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B/C), Payback Period (PBP) andsensitivity to chicken meat price changes, decreases of output prices and the production scale.This research applied case study method. Informants in this study are the owner, manager andemployees. The results showed that this business is feasible to be implemented with NPV valueof IDR 692,531,970 (positive), Net B/C of 2.90 (greater than one), IRR of 40% (greater thanSocial Opportunity Cost of Capital) and PBP of 4.9 (less than project life). Sensitivity analysison the increasing of raw material price of organic chicken meat is 39,80%, decrease ofproduction scale is 13,12% and decrease of output price is 12,36% equals to break even point, ifprice increases is above the percentage, then this business is not feasible to continue because theNPV < 0.